Differences in 18F-FDG Uptake and Expression of Glucose Transporter Between 2 Distinct Subtypes of Mass-Forming Intrahepatic Cholangiocarcinomas. (June 2020) - Kozaka, Kazuto; Kobayashi, Satoshi; Takamura, Hiroyuki; Sato, Yasunori; Kitao, Azusa; Inoue, Dai; Yoneda, Norihide; Tajima, Hidehiro; Kinuya, Seigo; Harada, Kenichi; Ohta, Tetsuo; Koda, Wataru; et al.
Abstract : Purpose: Recently, intrahepatic cholangiocarcinoma (iCCA) has been classified into small duct cholangiocarcinoma (SDC) and large duct cholangiocarcinoma (LDC) according to the origin of the biliary tree. Although the usefulness of 18 F-FDG PET/CT in iCCA is well known, there are no reports evaluating differences in accumulation of 18 F-FDG according to the recently described iCCA subtypes. The aim of this study was therefore to assess 18 F-FDG accumulation and the expression of glucose transporters in SDC and LDC. Methods: Our institutional review board approved this retrospective study and waived the requirement for informed consent. Fourteen consecutive surgically resected mass-forming iCCA (7 SDCs, 23 ± 6.7 mm; 7 LDCs, 44 ± 26 mm) were enrolled. The SUVmax on 18 F-FDG PET/CT and the expression of glucose transporter 1 (Glut-1), Glut-2, hexokinase 2 (HK2), and glucose-6-phosphatase by immunohistochemistry were evaluated and compared between SDC and LDC. Results: The SUVmax in SDC was significantly lower than that in LDC (3.2 ± 0.8 vs 7.6 ± 3.2, P < 0.01). The staining scores of Glut-1 and HK2 were significantly lower in SDC than in LDC (0 vs 3 ± 1.4, P = 0.0034; 1.6 ± 1.1 vs 3.4 ± 1.1, P = 0.014, respectively). Expression levels of Glut-2 and glucose-6-phosphatase were variable and did not show a significant difference between SDC and LDC. Overall survival was significantly worse in LDC than in SDC ( P = 0.01). Conclusions: 18 F-FDG accumulation and Glut-1 and HK2 expression were significantly higher in LDC than in SDC. A low-glycolytic feature may be one of the characteristic findings of SDC.